Phase Angle as an Indicator of Depression in Maintenance Hemodialysis Patients - Li, Xin; Zhang, Kun; Guo, Qi; Ding, Wei; Niu, Jianying; Zhao, Junli; Zhang, Liming; Qi, Hualin; Zhang, Suhua; Yu, Chen (Kidney Diseases, 2024)
Introduction: Depression is a common psychiatric problem in maintenance hemodialysis (MHD) patients. Recent studies have begun to explore the relationship between body composition and depression. Phase angle (PhA), a core parameter for assessing body composition, has been observed to be associated with frailty and cognitive dysfunction. The aim of this study was to investigate the association between PhA and depression in MHD patients. Methods: This multicenter, cross-sectional study included 843 MHD patients from seven dialysis centers in Shanghai, China. Depressive symptoms were evaluated using the Patient Health Questionnaire (PHQ-9), with a score of ≥10 indicating depression. PhA was measured by bioelectrical impedance analysis. Nutritional status was assessed by malnutrition inflammation score (MIS). Multivariable logistic regression models were used to investigate the association between PhA and depression. Restricted cubic spline (RCS) analysis was utilized to examine the association. Receiver operating characteristic curve was used to identify the cut-off value of PhA for depression. Results: A total of 15.2% of patients (62.8% male, median age 66 years) had depression. Median PhA level (interquartile range) of depressed patients was 4.4° (3.9–4.9°) for males and 3.9° (3.2–4.7°) for females. There was a significant decrease in the prevalence of depression with increasing quartiles of PhA levels. In multivariable logistic regression analyses, after adjusting for age, sex, education level, spKt/V, dialysis vintage, Charlson comorbidity index, hemoglobin, and serum albumin, lower PhA levels (lowest quartile group) were significantly associated with depressive symptoms (adjusted odds ratio, 2.19; 95% confidence interval, 1.07 to 4.48), compared to higher PhA levels (highest quartile group). RCS analysis showed a relatively inverse linear association between PhA and depression. The optimal cut-off value of PhA for depression was 4.9° for males and 3.5° for females. Subgroup analyses validated the findings across patient characteristics, including age, sex, diabetes, education, and malnutrition. Conclusion: Our findings indicated an inverse association between PhA and depressive symptoms in Chinese MHD patients, suggesting that PhA could serve as a valuable indicator for assessing the risk of depression in this population. Further studies are needed to explore the potential of PhA as a prognostic tool and its implications for intervention strategies.